Faire l'Europe par la culture / Europäisierung durch Kultur Liber Amicorum François Genton - OTT, Herta-Luise; Rimasson-Fertin, Natacha; Nicklas, Thomas (EPURE, Éditions et presses universitaires de Reims, 2021)
The European Union is a unique institutional construction in history. Built and enlarged slowly and peacefully, with the aim of reconciling sworn enemies after two terrible wars by means of an economic alliance designed to create a lasting human understanding, it is today much more than a simple free trade area. What about European culture? How does it relate to the continent's economic and political integration projects? Constantly under development, constantly questioned, even contested, European culture is the subject of the studies gathered in this volume.